Cartoons as Conveyers of Scientific Knowledge - Veiga, Ana Paula Soares (Sustainability in Debate, 2015)
This essay shows how the illustrations created by Brazilian cartoonist Jean Galvão interact with texts and other materials aimed at the dissemination of science, while they keep their own graphic discourse and work as points of entry for readers to access scientific knowledge. This work concludes that cartoon illustrations can act as instruments for social inclusion and citizenship enhancement.